2012
DOI: 10.1186/1471-2164-13-81
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression profiles in the hippocampus and prefrontal cortex of type 2 diabetic rats

Abstract: BackgroundThere has been an increasing body of epidemiologic and biochemical evidence implying the role of cerebral insulin resistance in Alzheimer-type dementia. For a better understanding of the insulin effect on the central nervous system, we performed microarray-based global gene expression profiling in the hippocampus, striatum and prefrontal cortex of streptozotocin-induced and spontaneously diabetic Goto-Kakizaki rats as model animals for type 1 and type 2 diabetes, respectively.ResultsFollowing pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 54 publications
4
30
1
Order By: Relevance
“…Gal is an inhibitory neuropeptide that is widely expressed in the central and peripheral nervous systems in vertebrates [29]. It co-exists within neurons with several small molecular classical neurotransmitters [30] and exerts strong inhibitory actions on synaptic transmission by reducing the release of neurotransmitters [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gal is an inhibitory neuropeptide that is widely expressed in the central and peripheral nervous systems in vertebrates [29]. It co-exists within neurons with several small molecular classical neurotransmitters [30] and exerts strong inhibitory actions on synaptic transmission by reducing the release of neurotransmitters [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that Gal shows distinct up-regulation after pathological disturbance within the nervous system, such as peripheral nerve injury [33]. Moreover, improvement of cognitive functions has been reported in animals treated with Gal receptor antagonists [29]. The formation of the mammalian central nervous system requires the establishment of complex neural circuits between diverse arrays of neuronal subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent whole-genome profile study revealed that 30 genes from the hippocampus, including galanin, and 22 genes from the prefrontal cortex, including GAL 2 , were found to exhibit altered expression levels in type 2 diabetic rats compared with nondiabetic control rats, shedding further light on the complex role of insulin signaling in fine-tuning brain functions and its interactions with galanin systems (Abdul-Rahman et al, 2012).…”
Section: A Glucose Metabolism and Diabetesmentioning
confidence: 99%
“…Moreover, compared to non-diabetic Wistar rats, also non-obese insulin-resistant Goto-Kakizyki (GK) rats displayed reduced spatial memory, which was accompanied by reduced pre-synaptic markers and increased glial specific proteins in the hippocampus [131]. Altered expression of genes involved in neurotransmission (among others) was found in the cortex of GK rats [132], indicating that diabetes-induced synaptic alterations are not region specific. A recent publication also reported that, relative to controls, GK rats display learning and memory deficits in a Morris water maze that are proportional to the grade of insulin resistance, reduction in dendritic spine density and neuronal viability in CA1 of the hippocampus, and impaired insulin-stimulated Akt/CREB phathway [133], consistent with AD-like pathology.…”
mentioning
confidence: 99%